Pengembangan Bahan Ajar Elektronik Berbasis Kearifan Lokal Jenjang SD Kelas IV SDN No.228/VII Mandiangin Kabupaten Sarolangun - Tri Susanti; Shalahuddin Shalahuddin; Ika Aryastuti Nurhasanah (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the development of electronic teaching materials based on local wisdom using the Canva and Cap Cut applications to assess, design teaching materials based on local wisdom, improve the learning process in a more interesting way, so that students do not feel bored in class. There is also the aim of knowing the steps for making fairy tale teaching materials based on local wisdom. Theme 8, the area where I live, sub-theme 1, the environment where I live, knowing the quality, effectiveness of the product, student responses before using the product, after using the product. The research methodology uses (research and development/R&D) the ADDIE model (Analysis of the initial stages of product manufacturing planning, Design product planning, Develop product development, Implement use of products that have been validated, Evaluation assess the resulting product which has been tested to see whether the final result is more productive ). Data collection techniques include interviews, observation, validation, trials, questionnaires, documentation. The results of the research show that, teachers' assessment of local wisdom-based electronic teaching materials for 95% of students 91.25% of the criteria is very feasible. Based on student learning outcomes, an average score is obtained. 805 So electronic teaching materials based on local wisdom for classes. IV SDN NO 228 VII Mandiangi Sarolangun Regency received very good criteria